Yep, ordinary algebra. Divide both sides by the same value and the equation remains balanced. The

**LHS**still = the RHS. So divide away and enjoy.3 Answers · Science & Mathematics · 19/08/2020

Mistake had occurred in step 1): it should be

**LHS**=4^[5(x-3)]=2^[2*5(x-3)]=2^[10(x-3)] RHS=32^(2x)=2^[5*(2x)]=2^[10x] Thus, 10x-30=10x => -30=0 is a contradiction => the equation has no solution.5 Answers · Science & Mathematics · 11/03/2021

... side = (2^x)² - (2^x) * 2 + 1........... Put 2^x = a =>

**LHS**= a² - 2 a + 1 =>**LHS**= ( a - 1 )² Hence...2 Answers · Science & Mathematics · 17/04/2021

RHS = cot²(x)[csc³(x) - csc(x)] = cot²(x)csc(x)[csc²(x) - 1] = cot²(x)csc(x)cot²(x) = cot⁴(x)csc(x) =

**LHS**1 Answers · Science & Mathematics · 09/05/2020

RHS = 2tan(2x)sin²(x) = tan(2x){1 - [1 - 2sin²(x)]} = tan(2x)[1 - cos(2x)] = tan(2x) - tan(2x)cos(2x) = tan(2x) - sin(2x) =

**LHS**2 Answers · Science & Mathematics · 15/01/2021

... about the knife-edge. Assuming the third mass is on the

**LHS**, write 0.40kg*30cm + 0.30kg*(50cm - x) = 0.60kg*30cm solves to x = 30 cm ◄ (positive...1 Answers · Science & Mathematics · 10/03/2021

... - 3n - 1) P(1): 1² = 1/2(1)[6(1)² - 3(1) - 1]

**LHS**= 1 RHS = 1 Proposition P(1) is confirmed...3 Answers · Science & Mathematics · 20/01/2021

... as x² = (2.3 - x)*1.19 * 10 ^-7. Then put all on the

**LHS**. Then expand. Notice now that you have a quadratic of the form ...3 Answers · Science & Mathematics · 17/01/2021

...3 terms to evaluate: (3-6)x + (4-6)x + (5-6)x = 72. Simply the

**LHS**. What does it give? [ = -6x ] Then, solving for x ...2 Answers · Science & Mathematics · 11/11/2020

...reaction PCl3 + 3H2O = H3PO4 + 3HCl Cl on the

**LHS**has ON -1 so P has ON = +3 O has...1 Answers · Science & Mathematics · 12/01/2021